2018
DOI: 10.1108/jrim-07-2017-0059
|View full text |Cite
|
Sign up to set email alerts
|

Narrative persuasion in social media: an empirical study of luxury brand advertising

Abstract: Purpose This paper aims to investigate the effectiveness of social media communication in luxury brand advertising from a narrative persuasion perspective. Specific purposes are to examine how characteristics of a message giver (i.e. comprehension fluency, imagery fluency) and message receiver (i.e. transportability, need for affect) influence the narrative persuasion process which further affects consumers’ subsequent responses (i.e. positive affect, brand social networking services [SNS] attitudes and intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 77 publications
2
27
0
Order By: Relevance
“…Social media users co-create brands through storytelling and sharing personal experiences (Singh and Sonnenburg, 2012). Storytelling and narrative transportation fosters engagement with customers by stimulating dialogue and access, leading to increased attitudinal evaluations (Huang et al, 2018;Hatch and Schultz, 2010). As seen in Hewett et al (2016), this dialogue between brands and social media users can eventually create, or in some cases even destroy, value for the brand.…”
Section: Social Media Co-creationmentioning
confidence: 99%
“…Social media users co-create brands through storytelling and sharing personal experiences (Singh and Sonnenburg, 2012). Storytelling and narrative transportation fosters engagement with customers by stimulating dialogue and access, leading to increased attitudinal evaluations (Huang et al, 2018;Hatch and Schultz, 2010). As seen in Hewett et al (2016), this dialogue between brands and social media users can eventually create, or in some cases even destroy, value for the brand.…”
Section: Social Media Co-creationmentioning
confidence: 99%
“…Narrative or storytelling ads are one example of such ads that tend to generate stronger emotional responses and consumer engagement [10]. Recent studies on narrative advertising found that story ads are more probable to trigger emotions in viewers, also facial coding has shown that there are more chances that viewers will give expressions while watching a narrative format ad [11,12]. Generation Z use more digital channels as compared to their predecessors and their attention is divided between various devices and they prefer quick solutions as they have unlimited information access [13].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 400m users use this feature every day; and there are 700,000 sponsored posts or ads per day (Cohen, 2018). Thus, brands can deliver messages in different ways: static visual image or audio-visual, which for luxury brands is important to develop the comprehension and image fluency to gain positive responses (Huang et al , 2018; Kim et al , 2016). While many consider video advertising on social media intrusive (Belanche et al , 2017; Benes, 2018; Cohen, 2018; Jung et al , 2016; Nettles, 2018), surveys suggested that Instagram users watch 75 per cent of brand video posts completely (Erskine, 2018) indicating a high level of acceptance.…”
Section: Introductionmentioning
confidence: 99%